Clinical chemistry, immunology, and laboratory quality control : a comprehensive review for board preparation, certification, and clinical practice 2026-02-15T15:55:57+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - DasGupta, Amitava; Wahed, Amer (Elsevier, 2014)

(untitled)
All pathology residents must have a good command of clinical chemistry, toxicology, immunology, and laboratorystatistics to be successful pathologists, as well as to pass the American Board of Pathology examination. Clinicalchemistry, however, is a topic in which many senior medical students and pathology residents face challenges. Clinical Chemistry, Immunology and Laboratory Quality Control meets this challenge head on with a clear and easy-to-read presentation of core topics and detailed case studies that illustrate the application of clinical chemistry knowledge to everyday patterns